Distinct Places to Address Intimate Partner Violence. Issue 15 (August 2021) - Piscitelli, Anthony; Doherty, Sean; Francis, Stephanie
The concept of place can be used to address intimate partner violence (IPV). Place, to geographers, is a concept that helps explain how human experiences shape a sense of meaning surrounding locations. Using a grounded theory approach and qualitative interviews with service providers, we present a case study exploring how Brantford social service agencies apply placemaking strategies and take advantage of the elements of place to reduce the harm associated with IPV. Six themes arose in the interviews. Home, the women's shelter, courts, and schools were found to represent unique areas where placemaking strategies help to reduce harm. Hair salons emerged as a unique place to reach victims, whereas prison was a place that encouraged offenders to make changes. These themes show the concept of place has the potential to add insights into how IPV can be reduced and the traumas facing victims addressed.